‘Region’ in the Rye: Impact of Modern Military Barracks on Small-Town Infrastructure and Socio-Economic Life. Case Study of Seredžius in 1935–1940 - Kilinskas, Kęstutis (Lietuvos istorijos studijos, 2025)
The article investigates the changes taking place in Seredžius, a small town, from 1935 to 1940, after the Third Infantry Regiment of the Lithuanian Grand Duke Vytautas was deployed in the small town of Seredžius, and the construction of the military site inspired changes in the social and economic life of the small-town residents. The research was conducted on the basis of documents archived by the Armed Forces of the Republic of Lithuania, Seredžius Volost (administrative unit of the time) and Kaunas Region (County) Administrator as well as military mass media publications.The research revealed that the introduction of a military barracks complex, denoted by its modern architecture (although the initial plan was never fully brought to life) and the arrival of the garrison not only changed the conditions of life but also became an example of modern architecture and innovative conditions of life for the small-town residents. The military barracks provided a space and opportunity for the minor town to introduce attributes of urban culture, such as theatre, concerts, sports, and tourism, followed by the introduction of the use of State symbols, which, along with festive rituals, were shaping the relationship of the town residents with the State and introduced some urban dynamism into the traditional rural space.What concerns the infrastructure, the introduction of the military barracks improved the connection for the residents of Seredžius with a larger town, Kėdainiai. It also created conditions for electricity connection. A fire brigade was set up, and kindergarten service was being offered – Seredžius as a minor town could not have afforded this infrastructure by itself. When modern military barracks were set up, this highlighted that Seredžius was lagging behind, that its residents had been badly suffering from poor conditions of life, and that social infrastructure was missing, the small town was financially weak, and the level of work/craft skills of the local residents was relatively poor. The town residents were only able to satisfy the minimal needs of the military unit: washing, tidying, cooking and delivery of goods. Thus, ultimately, the local residents were serving the officer corps of a higher social status. Thus, the locals became as if recipients of a peculiar type of guardianship by the officers in the cultural life.
Keywords: small town; military barracks; modernization; Seredžius; Lithuania in 1918–1940